Focusing surface acoustic waves assisted electrochemical detector in microfluidics. Issue 10 (11th November 2019) - Zheng, Tengfei; Liu, Yue; Xu, Chaoping; Lu, Haiwei; Wang, Chaohui
Abstract: This article demonstrates a novel electrochemical detection device. The device is composed by two focusing interdigital transducers for exciting focused surface acoustic waves by applying an AC signal, a three‐electrode system for electrochemical measurement, and a liquid pool for holding liquid on a LiNbO3 wafer. The amperometry current of ferrocenecarboxylic acid and potassium phosphate buffer solution is used to characterize the detection sensitivity. Two experiments are carried out to optimize the device design. The result shows that the two focusing interdigital transducers with arc degree 30° and distance 5 mm can remarkably enhance the liquid mixing rate. Under this condition, the oxidation current is about 27 times larger than that without surface acoustic wave stirring.